The Priority of the Via Negativa in Anselm’s Monologion - Hinton, Timothy (Philosophy & theology, 2008)
In this paper, I intend to demonstrate that in the Monologion Saint Anselm affirms the priority of the via negativa over the via positiva. More precisely, I shall argue that in that text Anselm defends a distinctive thesis with three components. There is, to begin with, a semantic component, according to which, all of our words for God—including those purporting to tell us what God is—fall utterly short of their mark. A consequence of this is that none of our speech is capable of describing the reality that is God. There is, in addition, an epistemic component according to which there is no way for us to understand what God is; we can only know what God is not. In consequence, we have no way of directly grasping God or of comprehending God’s being. Finally there is a metaphysical component according to which what God is in himself is an infinite and ineffable mystery. A consequence of this would be that God turns out to have nothing at all in common with his creatures.